2014
DOI: 10.1177/1721727x1401200209
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of 25-Hydroxyvitamin D Level and New Cytokines in Neonatal Sepsis

Abstract: The aim of this study was to evaluate diagnostic value of 25-hydroxyvitamin D level, Upar, IL-33 and ST2 in comparison with C-reactive protein, TNF-a and Interleukin-6 in neonatal sepsis. A total of 106 term babies were included 20 of whom were the control group. We used only data of high probable sepsis with blood culture positive infants, therefore 46 infants were excluded. Blood was collected from infants from the first day of sepsis (l.value) and 48-72 hours later (2.value). There were significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Although articles were searched from inception to 2019, articles published from 2014 to 2019 were eligible for the final analysis of this study. Regarding the quality scores of the studies, most had medium quality(Aye et al, 2018;Çekmez et al, 2014;Cetinkaya et al, 2015;Cizmeci et al, 2015;Dhandai et al, 2018;Dinlen et al, 2016;El-Kader et al, 2018;Gad et al, 2015;Gamal et al, 2017;Mokhtar et al, 2018;Ozdemir & Cag, 2019;Sarwade, 2019;Say et al, 2017;Tayel et al, 2018;Uday et al, 2016;Yang et al, 2016), whereas one was classified under the low(Kumar et al, 2019) and high(Agrawal et al, 2019) quality category each.3.3 | The prevalence of vitamin D deficiency among neonatesIn the present study, vitamin D deficiency was declared when cord blood was less than 20ng/ml(Chang & Lee, 2019). Eleven studies(Agrawal et al, 2019;Aye et al, 2018;Cetinkaya et al, 2015;Cizmeci et al, 2015;Dhandai et al, 2018;Dinlen et al, 2016;Gad et al, 2015;Kumar et al, 2019;Mokhtar et al, 2018;Ozdemir & Cag, 2019;Say et al, 2017) were eligible to compute the pooled…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Although articles were searched from inception to 2019, articles published from 2014 to 2019 were eligible for the final analysis of this study. Regarding the quality scores of the studies, most had medium quality(Aye et al, 2018;Çekmez et al, 2014;Cetinkaya et al, 2015;Cizmeci et al, 2015;Dhandai et al, 2018;Dinlen et al, 2016;El-Kader et al, 2018;Gad et al, 2015;Gamal et al, 2017;Mokhtar et al, 2018;Ozdemir & Cag, 2019;Sarwade, 2019;Say et al, 2017;Tayel et al, 2018;Uday et al, 2016;Yang et al, 2016), whereas one was classified under the low(Kumar et al, 2019) and high(Agrawal et al, 2019) quality category each.3.3 | The prevalence of vitamin D deficiency among neonatesIn the present study, vitamin D deficiency was declared when cord blood was less than 20ng/ml(Chang & Lee, 2019). Eleven studies(Agrawal et al, 2019;Aye et al, 2018;Cetinkaya et al, 2015;Cizmeci et al, 2015;Dhandai et al, 2018;Dinlen et al, 2016;Gad et al, 2015;Kumar et al, 2019;Mokhtar et al, 2018;Ozdemir & Cag, 2019;Say et al, 2017) were eligible to compute the pooled…”
mentioning
confidence: 60%
“…Finally, a total of 18 articles(Agrawal et al, 2019;Aye et al, 2018;Çekmez et al, 2014;Cetinkaya et al, 2015;Cizmeci et al, 2015;Dhandai et al, 2018;Dinlen et al, 2016;El-Kader et al, 2018;Gad et al, 2015;Gamal et al, 2017;Kumar et al, 2019;Mokhtar et al, 2018;Ozdemir & Cag, 2019;Sarwade, 2019;Say et al, 2017;Tayel et al, 2018;Uday et al, 2016;Yang et al, 2016) were included in this systematic review and meta-analysis (Table1and Figure1).3.2 | Characteristics of the original studiesIn the current study, 12 case-control(Agrawal et al, 2019;Aye et al, 2018;Çekmez et al, 2014;Cizmeci et al, 2015;Dinlen et al, 2016;Gad et al, 2015;Gamal et al, 2017;Mokhtar et al, 2018;Sarwade, 2019;Say et al, 2017;Tayel et al, 2018;Yang et al, 2016) and six cohort(Cetinkaya et al, 2015;Dhandai et al, 2018;El- Kader et al, 2018;Kumar et al, 2019;Ozdemir & Cag, 2019;Uday et al, 2016) studies were included. Out of the included studies, six were from Turkey(Çekmez et al, 2014;Cetinkaya et al, 2015;Cizmeci et al, 2015;…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After a preliminary search, a total of 26 studies were identified, and 17 of them were weeded out by our exclusion criteria. Reading the title, abstract, and full text, the remaining six articles were included in our study ( 7 , 19–23 ). Figure 1 shows the selection progress.…”
Section: Resultsmentioning
confidence: 99%
“…The outcomes are illustrated in Figure 2 . Four studies ( 7 , 19 , 21 , 23 ) used a prospective study design that avoided inappropriate exclusion. The remaining articles with case–control design may exaggerate diagnostic accuracy.…”
Section: Resultsmentioning
confidence: 99%